Exposure of patients to di(2-ethylhexy)phthalate (DEHP) and its metabolite MEHP during extracorporeal membrane oxygenation (ECMO) therapy - Kaestner, Franziska; Seiler, Frederik; Rapp, Daniel; Eckert, Elisabeth; Müller, Johannes; Metz, Carlos; Bals, Robert; Drexler, Hans; Lepper, Philipp M.; Göen, Thomas (PLoS ONE, 2020)
The plasticizer di(2-ethylhexyl)phthalate (DEHP) is often used for PVC medical devices, that are also largely used for intensive care medical treatments, like extracorporeal membrane oxygenation (ECMO) therapy. Due to the toxicological potential of DEHP, the inner exposure of patients with this plasticizer is a strong matter of concern as many studies have shown a high leaching potential of DEHP into blood. In this study, the inner DEHP exposure of patients undergoing ECMO treatment was investigated. The determined DEHP blood levels of ECMO patients and the patients of the control group ranged from 31.5 to 1009 μg/L (median 156.0 μg/L) and from 19.4 to 75.3 μg/L (median 36.4 μg/L), respectively. MEHP blood levels were determined to range from < LOD to 475 μg/L (median 15.9 μg/L) in ECMO patients and from < LOD to 9.9 μg/L (median 3.7 μg/L) in the control group patients, respectively. Increased DEHP exposure was associated with the number of cannulas and membranes of the ECMO setting, whereas residual diuresis decreased the exposure. Due to the suspected toxicological potential of DEHP, its use in medical devices should be further investigated, in particular for ICU patients with long-term exposure to PVC, like in ECMO therapy.
CRIS-Team Scopus Importer:2020-02-11

External Quality Assurance Schemes (EQUASs) and Inter-laboratory Comparison Investigations (ICIs) for human biomonitoring of polycyclic aromatic hydrocarbon (PAH) biomarkers in urine as part of the quality assurance programme under HBM4EU - Nübler, Stefanie; Esteban López, Marta; Castaño, Argelia; Mol, Hans G.J.; Müller, Johannes; Schäfer, Moritz; Haji-Abbas-Zarrabi, Karin; Hajslova, Jana; Pulkrabova, Jana; Dvorakova, Darina; Urbancova, Katerina; Koch, Holger M.; et al. (International Journal of Hygiene and Environmental Health, 2023)
Polycyclic aromatic hydrocarbons (PAHs) were included as priority substances for human biomonitoring (HBM) in the European Human Biomonitoring Initiative (HBM4EU), which intended to harmonise and advance HBM across Europe. For this project, a specific Quality Assurance and Quality Control (QA/QC) programme applying Inter-laboratory Comparison Investigations (ICIs) and External Quality Assurance Schemes (EQUASs) was developed to ensure the comparability and accuracy of participating analytical laboratories. This paper presents the results of four ICI/EQUAS rounds for the determination of 13 PAH metabolites in urine, i.e. 1-naphthol, 2-naphthol, 1,2-dihydroxynaphthalene, 2-, 3- and 9-hydroxyfluorene, 1-, 2-, 3-, 4- and 9-hydroxyphenanthrene, 1-hydroxypyrene and 3-hydroxybenzo(a)pyrene. However, 4 PAH metabolites could not be evaluated as the analytical capacity of participating laboratories was too low. Across all rounds and biomarkers, 86% of the participants achieved satisfactory results, although low limits of quantification were required to quantify the urinary metabolites at exposure levels of the general population. Using high-performance liquid or gas chromatography coupled with mass spectrometry (HPLC-MS; GC-MS) and isotope dilution for calibration as well as performing an enzymatic deconjugation step proved to be favourable for the accurate determination of PAHs in urine. Finally, the HBM4EU QA/QC programme identified an international network of laboratories providing comparable results in the analysis of urinary PAH biomarkers, although covering all parameters initially selected was still too challenging.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 1-Hydroxypyrene; Analytical method; HBM4EU; Human biomonitoring; Quality control; Z-score

External quality assurance schemes (EQUASs) and interlaboratory comparison investigations (ICIs) for the human biomonitoring of aromatic amines in urine as part of the quality assurance programme under HBM4EU. - Nübler, Stefanie; Burkhardt, Therese; Schäfer, Moritz; Müller, Johannes; Haji-Abbas-Zarrabi, Karin; Pluym, Nikola; Scherer, Max; Scherer, Gerhard; Esteban-López, Marta; Castaño, Argelia; Mol, Hans G.J.; Koch, Holger M.; et al. (Analytical Methods, 2024)
Exposure to aromatic amines may occur via tobacco smoke, hair dyes or tattoo inks, but also in the workplace during certain manufacturing processes. As some aromatic amines are known or suspected carcinogens, human biomonitoring (HBM) is essential to assess their exposure. Aromatic amines were among the selected chemicals in HBM4EU, a European-wide project to harmonise and advance HBM within 30 European countries. For this purpose, the analytical comparability and accuracy of participating laboratories were assessed by a QA/QC programme comprising interlaboratory comparison investigations (ICIs) and external quality assurance schemes (EQUASs). This paper presents the evaluation process and discusses the results of three ICI/EQUAS rounds for the determination of aromatic amines in urine conducted in 2019 and 2020. The final evaluation included ten participants which analysed the following six targeted aromatic amines over three rounds: aniline, ortho-toluidine (TOL), 4,4'-methylenedianiline (MDA), 4,4'-methylenebis(2-chloroaniline) (MOCA), 2,4-diaminotoluene (2,4-TDA), and 2,6-diaminotoluene (2,6-TDA). Most participants achieved satisfactory and highly comparable results, although low quantification limits were required to quantify the parameters at the level of exposure in the general population. Hydrolysis of the sample followed by liquid-liquid extraction and subsequent analysis of the derivatised analytes by means of GC-MS/MS were preferred for the sensitive and precise determination of aromatic amines in urine. This QA/QC programme succeeded in establishing a network of laboratories with high analytical comparability and accuracy for the analysis of aromatic amines in Europe.
EVALuna2:577007

HBM4EU chromates study – PFAS exposure in electroplaters and bystanders - Göen, Thomas; Abballe, Annalisa; Bousoumah, Radia; Godderis, Lode; Iavicoli, Ivo; Ingelido, Anna Maria; Leso, Veruscka; Müller, Johannes; Ndaw, Sophie; Porras, Simo P.; Verdonck, Jelle; Santonen, Tiina; et al. (Chemosphere, 2024)
The study aims to reveal the exposure to perfluoroalkyl substances (PFAS) in workers in different industry sectors with exposures to hexavalent chromium (Cr(VI)). The PFAS exposure of in total 172 individuals from 4 countries was assessed by the determination of 8 perfluoroalkyl carboxylic acids and 4 perfluoroalkyl sulfonic acids in plasma samples. The participants were 52 chrome plating workers, 43 welders, 3 surface treating workers and 74 workers without any occupational Cr exposure as controls. Significant differences between workers with Cr exposure and controls were found for the perfluoroalkyl sulfonic acids, particularly for perfluorooctane sulfonic acid (PFOS). The median and maximum levels were, respectively, 4.83 and 789 μg/l for chrome plating workers, 4.97 and 1513 μg/l for welders, and 3.65 and 13.9 μg/l for controls. The considerably high PFOS exposure in Cr platers and welders can be explained by the former application of PFOS as mist suppressants in electroplating baths, which resulted in an exposure of the directly involved operators, but also of welders performing maintenance and repair service at these workplaces.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Bystanders; Human biomonitoring; Occupational exposure; Perfluoroalkyl substances; Persistent substances

Interlaboratory Comparison Investigations (ICIs) and External Quality Assurance Schemes (EQUASs) for human biomonitoring of perfluoroalkyl substances (PFASs) in serum as part of the quality assurance programme under HBM4EU - Nübler, Stefanie; Esteban López, Marta; Castaño, Argelia; Mol, Hans G.J.; Haji-Abbas-Zarrabi, Karin; Schäfer, Moritz; Müller, Johannes; Hajslova, Jana; Dvorakova, Darina; Antignac, Jean Philippe; Koch, Holger M.; Haug, Line Småstuen; et al. (Science of the Total Environment, 2022)
Perfluoroalkyl substances (PFASs) are of very high concern due to their persistence and accumulative behaviour as well as their manifold adverse health effects. Human biomonitoring (HBM) based on the determination of PFASs in serum samples is an adequate and established strategy for exposure and risk assessment of the population. The suspected health risks associated with exposure levels in the general population call for reliable HBM data verified by Quality Assurance and Quality Control (QA/QC) measures. PFASs were among the chemicals selected as priority substances in HBM4EU, a pan-European project to harmonize and advance HBM within 30 European countries. For this purpose, the analytical comparability and accuracy of PFASs-analysing laboratories was assessed in a QA/QC programme comprising Interlaboratory Comparison Investigations (ICIs) and External Quality Assurance Schemes (EQUASs). This paper presents the evaluation process and discusses the results of four ICI/EQUAS rounds for the determination of eight perfluoroalkyl carboxylic acids and four perfluoroalkyl sulfonic acids (PFBS, PFHxS, PFHpS, PFOS) in serum. All 21 participating laboratories achieved satisfactory results for at least six of these biomarkers, although low limits of quantification (of about 0.1 μg/L) were required to quantify serum PFAS levels at general population exposure levels. The mean relative standard deviation of the participants' results (study RSDR) significantly improved from 22 % to 13 % over all PFAS biomarkers in the course of the four rounds. This QA/QC programme succeeded in establishing a network of laboratories with high analytical comparability and accuracy for the analysis of PFASs across 12 European countries.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Analytical methods; HBM4EU; Internal exposure; Perfluoroalkyl carboxylic acids; Perfluoroalkyl sulfonic acid; Z-scores

Plasma Nitrate and Incidence of Cardiovascular Disease and All-Cause Mortality in the Community: The Framingham Offspring Study - Maas, Renke; Xanthakis, Vanessa; Göen, Thomas; Müller, Johannes; Schwedhelm, Edzard; Boeger, Rainer H.; Vasan, Ramachandran S. (Journal of the American Heart Association, 2017)
Nitrate is a dietary component as well as an endogenously formed metabolite and source of the signaling molecule nitric oxide. Harmful as well as beneficial effects of nitrate have been advocated. Data regarding the prognostic relevance of plasma nitrate are limited. The aim of this study was to evaluate the prospective association of plasma nitrate with cardiovascular disease (CVD) and all-cause mortality.We assayed plasma nitrate in 2855 Framingham Offspring Study participants (mean age 59 years, 54% women) by gas chromatography-mass spectrometry and evaluated its association with all-cause mortality and incident CVD. On follow-up (median 17.3 years), 775 participants died and 522 developed new-onset CVD (of 2546 participants free of CVD at baseline). In multivariable models adjusting for standard risk factors, plasma nitrate was associated with an increased risk of death in participants (hazard ratio per unit increase in log-nitrate 1.21; 95% confidence interval, 1.04-1.40 [P=0.015]). The strength of the association was attenuated by additional adjustment for estimated glomerular filtration rate (hazard ratio, 1.16; 95% confidence interval, 1.00-1.35 [P=0.057]). In contrast, no evidence was found for an association of plasma nitrate with incident CVD (multivariable-adjusted hazard ratio per unit increase log-nitrate 1.08; 95% confidence interval, 0.89-1.31 [P=0.42]).In our prospective community-based investigation, a higher plasma nitrate concentration was associated with all-cause mortality but not with incident CVD. The association of nitrate with mortality may at least in part be attributable to its association with renal function.
EVALuna2:9774

Plasticizer exposure of infants during cardiac surgery - Eckert, Elisabeth; Müller, Johannes; Höllerer, Christine; Purbojo, Ariawan; Cesnjevar, Robert; Göen, Thomas; Münch, Frank (Toxicology Letters, 2020)
In the present study we investigated the internal exposure situation of infant patients to the plasticizers TEHTM (tri-2-ethylhexyl trimellitate) and DEHP (di-2-ethylhexyl phthalate). The study collective included 21 infant patients aged 2–22 months that had to undergo cardiac surgery using cardio pulmonary bypass (CPB). Each patient, but one, received blood products during surgery. A special feature was that the used CPB tubings were exclusively plasticized with the alternative plasticizer TEHTM and were free of the standard plasticizer DEHP, that raises increasing toxicological concern. The blood products were stored in DEHP plasticized blood bags. Blood and urine samples of each infant patient were analysed before and after the surgery for the levels of the plasticizers DEHP and TEHTM and their metabolites. In general, the plasticizers were detected in the post-surgery blood samples only, with TEHTM in low levels (median 18.4 μg/L) and DEHP in rather elevated levels (median 1046 μg/L). With respect to the urine samples, TEHTM metabolites were not detected in any of the samples. DEHP metabolites were found in all urine samples, however, in significantly increased median levels in the post-surgery urine samples of the infants (increase factor 5–26). Thus, the present study clearly demonstrates the strong contribution of standard medical procedures to the internal plasticizer burden of patients. Particularly with regard to the suspected endocrine disrupting activities of the phthalate plasticizer DEHP, the elevated internal levels of this plasticizer and its metabolites in infants following cardiac surgery are alarming.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Biomonitoring; Cardio pulmonary bypass; DEHP; Medical devices; Packed red blood cells; TOTM; Urine

Simultaneous determination of polyvinylchloride plasticizers di(2-ethylhexyl) phthalate and tri(2-ethylhexyl) trimellitate and its degradation products in blood by liquid chromatography-tandem mass spectrometry - Eckert, Elisabeth; Müller, Johannes; Göen, Thomas (Journal of Chromatography A, 2015)
Di(2-ethylhexyl) phthalate (DEHP) and tri(2-ethylhexyl) trimellitate (TEHTM or TOTM) are common plasticizers that are also largely used for PVC medical devices, e.g. bags and tubing for blood transfusions and infusions. The leachability of medical devices is a well-known situation of increasing toxicological concern. To assess the migration of plasticizers from PVC medical devices into human blood we developed and validated an analytical method for the determination of DEHP and TOTM in combination with the determination of their primary degradation products mono(2-ethylhexyl) phthalate (MEHP), 1,2-di(2-ethylhexyl) trimellitate (1,2-DEHTM) and 2-mono(2-ethylhexyl) trimellitate (2-MEHTM). The presented method involves liquid-liquid extraction of the analytes from the blood followed by the subsequent analytical separation and detection using LC-MS/MS analysis. The validation of the procedure showed a good precision in the range of 1.8 to 5.3%. Mean accuracy ranged from 86% for 1,2-DEHTM to 109% for MEHP. LOQ was found to be 2 to 5?g/L for each of the analytes. Additionally, the method is characterised by its wide linear range up to 2mg/L each for the degradation products of TOTM to 100mg/L for the parent plasticizer DEHP. The presented method promises to be of major advantage for further studies as it allows for the first time the simultaneous determination of DEHP and TOTM in human blood in combination with the analysis of their degradation products that render possible to investigate the leachability of a broad range of PVC medical devices in human blood using only one analytical method.
EVALuna2:9732